The response of coral skeletal nano-structure and hardness to ocean acidification conditions - Tan, Chao Dun; Haehner, Georg; Fitzer, Susan; Cole, Catherine Sarah; Finch, Adrian Anthony; Hintz, Christopher James; Hintz, Kenneth; Allison, Nicola (Royal Society Open Science, 2023)
Ocean acidification typically reduces coral calcification rates and can fundamentally alter skeletal morphology. We use atomic force microscopy (AFM) and microindentation to determine how seawater pCO 2 affects skeletal structure and Vickers hardness in a Porites lutea coral. At 400 µatm, the skeletal fasciculi are composed of tightly packed bundles of acicular crystals composed of quadrilateral nanograins, approximately 80–300 nm in dimensions. We interpret high adhesion at the nanograin edges as an organic coating. At 750 µatm the crystals are less regular in width and orientation and composed of either smaller/more rounded nanograins than observed at 400 µatm or of larger areas with little variation in adhesion. Coral aragonite may form via ion-by-ion attachment to the existing skeleton or via conversion of amorphous calcium carbonate precursors. Changes in nanoparticle morphology could reflect variations in the sizes of nanoparticles produced by each crystallization pathway or in the contributions of each pathway to biomineralization. We observe no significant variation in Vickers hardness between skeletons cultured at different seawater pCO 2 . Either the nanograin size does not affect skeletal hardness or the effect is offset by other changes in the skeleton, e.g. increases in skeletal organic material as reported in previous studies.